Feasibility of pig and human‐derived aortic valve interstitial cells seeding on fixative‐free decellularized animal pericardium. Issue 2 (23rd March 2015) - Santoro, Rosaria; Consolo, Filippo; Spiccia, Marco; Piola, Marco; Kassem, Samer; Prandi, Francesca; Vinci, Maria Cristina; Forti, Elisa; Polvani, Gianluca; Fiore, Gianfranco Beniamino; Soncini, Monica; Pesce, Maurizio
Abstract: Glutaraldehyde‐fixed pericardium of animal origin is the elective material for the fabrication of bio‐prosthetic valves for surgical replacement of insufficient/stenotic cardiac valves. However, the pericardial tissue employed to this aim undergoes severe calcification due to chronic inflammation resulting from a non‐complete immunological compatibility of the animal‐derived pericardial tissue resulting from failure to remove animal‐derived xeno‐antigens. In the mid/long‐term, this leads to structural deterioration, mechanical failure, and prosthesis leaflets rupture, with consequent need for re‐intervention. In the search for novel procedures to maximize biological compatibility of the pericardial tissue into immunocompetent background, we have recently devised a procedure to decellularize the human pericardium as an alternative to fixation with aldehydes. In the present contribution, we used this procedure to derive sheets of decellularized pig pericardium. The decellularized tissue was first tested for the presence of 1, 3 α‐galactose (αGal), one of the main xenoantigens involved in prosthetic valve rejection, as well as for mechanical tensile behavior and distensibility, and finally seeded with pig‐ and human‐derived aortic valve interstitial cells. We demonstrate that the decellularization procedure removed the αGAL antigen, maintained the mechanical characteristics of the native pig pericardium, and ensured an efficient surface colonization of the tissue by animal‐ and human‐derived aortic valve interstitial cells. This establishes, for the first time, the feasibility of fixative‐free pericardial tissue seeding with valve competent cells for derivation of tissue engineered heart valve leaflets. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 345–356, 2016.